CONFLICT MANAGEMENT STRATEGIES IN WORK TEAMS IN THE CREATIVE INDUSTRY - Abu Muna Almaududi Ausat; Andriya Risdwiyanto; Muh. Arfah; Jemadi Jemadi (KENDALI: Economics and Social Humanities, 2023)
Conflict in work teams is a natural occurrence due to differences in individual backgrounds, views, and preferences. However, conflicts that are not handled properly can cause detrimental impacts, such as decreased productivity, quality, and job satisfaction. This study aims to identify the most effective conflict management strategies in work teams in the creative industry and analyse the factors that influence them. This research is qualitative in nature. Data collection techniques included listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study concluded that effective conflict management strategies are essential to improve productivity, quality, and job satisfaction in teams in the creative industry. Open and honest communication, collaboration, compromise, and mediation are some of the effective conflict management strategies in the context of the creative industry.